(untitled) (Experimental biology, 2025)
The genus Iris Tourn. ex L is one of the largest genera of the family Iridaceae Juss. and the whole order Asparagales, attractive for its highly ornamental properties. The object of this study is a red-book species – Iris kuschakewiczii B. Fedtsch., a representative of bulbous irises, as well as subgenus Scorpiris Spach, which was reintroduced to the genus Iris from Juno Tratt. Materials of expedition trips and herbarium sheets from domestic and foreign collection funds were analyzed: Institute of Botany and Phytointroduction (AA, Almaty, Kazakhstan), Lomonosov Moscow State University (MW, Moscow, Russia), V. L. Komarov Botanical Institute (LE, St. Petersburg, Russia), Institute of Botany, Academy of Sciences of the Republic of Uzbekistan (TASH, Tashkent, Uzbekistan), Institute of Plant Biology and Biotechnology (IPBB, Almaty, Kazakhstan), New York Botanical Garden (NY, New York, USA), University of Michigan (MICH, Michigan, USA), Kew Herbarium, Royal Botanic Gardens (K, London, England).